PENCEGAHAN HIPERTENSI MELALUI EDUKASI TERSTRUKTUR CERDIK: RURAL AREA - Suhariyanto, Suhariyanto; Fahrul Razi, Yadi; Barlia, Gusti; Fittarsih, Niya (Jurnal Keperawatan Widya Gantari Indonesia, 2024)
Health promotion can reduce the impact of risk factors related to the broad determinants of health that lead to disease and improve the quality of life of individuals and communities. Hypertension, which is often referred to as a silent killer, is the most common disease experienced by the elderly and is the number one cause of death in the world. The impact that occurs on hypertension sufferers is such as physiological impact and physical impact. The CERDIK program can be carried out through education in a structured manner. Structured means that the educational material is prepared properly in accordance with the goals to be achieved. Structured according to the great Indonesian dictionary is already in a state of being arranged or neatly arranged. Lack of knowledge can lead to hypertension. The purpose of the study is to determine the effectiveness of CERDIK structured education on increasing knowledge in the prevention of hypertension. . The type of research is Pre experiment design with pre and post test without control group design. The population in the study is respondents who have hypertension or have a history of hypertension. Sampling used consecutive sampling techniques and using the standard deviation formula, the sample totaled 13 people. The results of this study showed that knowledge before the intervention had a score of 61.92 and after being given health education showed a score of 87.46 using the Wilcoxon statistical test which showed that there was an influence of CERDIK structured education on the improvement of knowledge in the prevention of hypertension in the working area of the Simpang Empang Health Center, Tangaran District, especially in Pancur Village, with p = 0.001. It is recommended to the Health Center to provide health education about hypertension prevention through CERDIK structured education for hypertensive patients and those who have a history of hypertension in health education.